PENINGKATAN KEMAMPUAN BERFIKIR KRITIS DALAM PERSIAPAN MENGIKUTI PENDIDIKAN LEBIH LANJUT DAN MENGHADAPI DUNIA KERJA STUDI KASUS : SMK ISLAM ASSA’ADATUL ADABIYAH - Winarti, Euis; Badriyah, Badriyah; Lutviani, Metya; Kuswandi, Kuswandi; Fajriah, Nurul; Irza, Lydia Nur (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to evaluate the effectiveness of strategies and programs designed to improve critical thinking skills in individuals in preparation for further education and facing the challenges of the world of work. This research was conducted involving a group of participants consisting of vocational school students who were in class The research methods used include literature analysis, surveys, observations and implementation of special training programs focused on developing critical thinking. Surveys were conducted before and after the training to measure changes in participants' critical thinking abilities. Survey results and qualitative data from training sessions were analyzed to evaluate the program's impact. The conclusion of this research and community service activity is that OTKP Vocational School students can improve their ability to think critically so they can make decisions in the future whether they choose to continue their education at college or choose to look for work. LP3I Jakarta Polytechnic as one of the tertiary institutions has an active role in providing understanding to the community so that people know more about vocational education. One way is to provide seminars like this to build public awareness and understanding of the importance of the world of education, especially vocational education in tertiary institutions Keyword : Critical Thinking Skill, Further Education, Preparation For The World Of Work